Efeito de consequências culturais de naturezas diferentes sobre um culturante - PAIXÃO JUNIOR, Francisco Denilson (Universidade Federal do Pará, 2019)
The concept of metacontingency describes functional relations between interlocking contingencies (with their aggregate products) and cultural contingencies. We call culturant the recurrent unit of interlocking behavioral contingencies and their aggregate products. For more than a decade ago, behavior analysts have been dedicated to make the experimental evaluation of metacontingency’s relations. Current studies verified that verbal cultural consequences correlated with non-verbal cultural consequences produce more rate of recurrence of culturants than just cultural consequences of one nature only. However, the differential effects of cultural consequences dependent of the changes in experimental condiction on a culturant are unknown. This study evaluated the differential effect of cultural consequences of different natures (correlated or not) on a target culturant from an experimental preparation that applied an analogous ABAB single-subject design in a task of choosing color lines in a matrix. The dates suggests that there are more favorable conditions for the selection and maintenance of culturants than others and that stereotyped patterns of choices emerge under conditions of high stability of culturant recurrence. This study also has light on possibilities of studies related to uncontrollable aversive conditions and their effects on culturante.